2020
DOI: 10.21653/tjpr.547050
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Thigh Muscle Activations in Bridge-Plank Exercises Performed on Different Grounds

Abstract: The study aimed to examine hamstring-quadriceps muscle activations of the supine bridge and reverse plank exercises that are performed for both improving the overall body strength and contributing to the treatment in the process following an injury on different grounds. Methods: Ten participants (four males and six females, age=26.70±3.02 years) without regular sports habits were included in the study. Bilateral supine bridge and bilateral reverse plank exercises were practiced randomly on stable and unstable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A previous study reported that the traditional plank engages the anterior stabilizers while the reverse plank engages the posterior stabilizers, including the multifidus, which is easily affected by the direction of gravity due to the supine posture [ 23 ]. Additionally, the reverse plank facilitates the strengthening of the muscles of the upper and lower extremities, including the scapular depressors and retractors, elbow extensors, posterior deltoids, gluteus, and hamstrings [ 24 , 25 , 26 ]. It can also be used as a rehabilitation exercise to improve core and spinal stabilization by engaging both the abdominals and lower back muscles.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that the traditional plank engages the anterior stabilizers while the reverse plank engages the posterior stabilizers, including the multifidus, which is easily affected by the direction of gravity due to the supine posture [ 23 ]. Additionally, the reverse plank facilitates the strengthening of the muscles of the upper and lower extremities, including the scapular depressors and retractors, elbow extensors, posterior deltoids, gluteus, and hamstrings [ 24 , 25 , 26 ]. It can also be used as a rehabilitation exercise to improve core and spinal stabilization by engaging both the abdominals and lower back muscles.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to compare different practices in order to design the right exercises for strength and conditioning training. The appropriate exercise choice is possible using the activation values determined during different exercises for the same muscle or muscle group [8,9]. The findings obtained may be followed by exercise participants for their current training situations or targeted goals.…”
mentioning
confidence: 99%